PP42 Perceptions and experiences of wellbeing provision for NHS ambulance staff: a qualitative interview study of wellbeing leads and frontline staff. Issue 9 (23rd August 2022) - Phung, Viet-Hai; Pritchard, Gary; Sanderson, Kristy; Bell, Fiona; Hird, Kelly; Wankhade, Paresh; Asghar, Zahid; Siriwardena, Niro
Abstract : Background: The wellbeing of ambulance staff is critical to their safety and safe care delivery. This study examined the perceptions of English NHS ambulance Trust health and wellbeing leads, and the experiences of UK ambulance staff of workplace wellbeing culture and provision. Methods: Semi-structured telephone interviews were undertaken with staff wellbeing leads for eight NHS ambulance trusts in England and with ambulance staff from three NHS ambulance trusts in England, selected to represent services with high, medium or low relative sickness absence rates. Interviews were subsequently transcribed, coded and analysed using Framework Analysis (FA). Results: We interviewed eight wellbeing leads and 25 frontline ambulance staff from April-November 2020. Decisions around what was included in or omitted from wellbeing policies sometimes led to conflict between wellbeing leads and their superiors. Ambulance work was perceived as inherently unhealthy because of work stress and the risk of encountering traumatic incidents. Well-being leads understood the adverse impacts of work on mental health for some staff. Ambulance staff wanted empathy, understanding and practical support from managers, but the reality did not always match these needs, because of variability in provision and experiences of health and wellbeing services, poor behaviours or attitudes from line managers, and a stigmatising rather than open organisational culture. COVID-19 not only impacted significantly on staff health and wellbeing, but also challenged how ambulance trusts support them. Conclusions: The importance of an open organisational culture and the variable availability and experiences of interventions to support staff to stay well at work means that improvements are needed in both to ensure positive staff mental health and wellbeing. Early interventions, improved training for line managers to support staff at work, bespoke wellbeing services and an open culture are key to delivering effective support to ambulance staff, especially in the light of the COVID-19 pandemic.